Effect of different training workload on overhead throwing performance with different weighted balls - van den Tillaar, R.; Marques, M. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to investigate the effect of a single and a double training workload with 3-kg medicine ball on the throwing speed in 2-handed overhead throwing movement. Second, what the effect of training with 3-kg medicine balls had on throwing speed with other ball weights. Forty high school students (age 15.9 ± 1.0 year, mass 60.9 ± 9 kg, height 1.68 ± 0.08 m), divided into 3 speed-matched groups, participated in the study. The first group was a control group and did not train any throwing program regimen, whereas the other 2 groups trained overhead throwing with a single (3 series of 6 throws with a 3-kg medicine ball) or double training workload (6 series of 6 throws with a 3-kg medicine ball) for 6 weeks. Throwing speed with 0.35-, 0.45-, 1-, and 3-kg medicine balls was tested before and after a training period of 6 weeks with 2 sessions per week. A significant (p = 0.05) increase in throwing speed was found after the 6-week training period with the 0.35- (5.1%), 1- (3.5%), and 3-kg medicine balls (5.2%) for both training groups, but not with the 0.45-kg ball (0.6%). This increase was mainly caused by the increase of the double workload group. This indicates that training workload is of importance in these subjects for enhancement of ball throwing performance and in designing training programs. Furthermore, that throwing with high enough training volume of throws with a 3-kg medicine ball also can increase ball speed with lighter balls.